Algorithm-architecture matching for signal and image processing best papers from Design and Architectures for Signal and Image Processing 2007 & 2008 & 2009 - Gogniat, Guy (Lecture Notes in Electrical Engineering, 2011)
Algorithm-Architecture Matching for Signal and Image Processing presents a collection of selected contributions from both industry and academia, addressing different aspects of Algorithm-Architecture Matching approach ranging from sensors to architectures design. The scope of this book reflects the diversity of potential algorithms, including signal, communication, image, video, 3D-Graphics implemented onto various architectures from FPGA to multiprocessor systems. Several synthesis and resource management techniques leveraging design optimizations are also described and applied to numerous algorithms.